Exploring Grammar through Small Group Interaction Technique on Pre-Intermediate Structure Course - Nurbianta Nurbianta; Rahmat Rahmat; Ashri Shollina (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2019)
The main purpose of this study is to investigate the students’ ability on structure course at the third semester of STIT Muhammadiyah, Tanjung Redeb. Teaching and learning process in mastering the grammatical of English was conducted through Small Group Interaction technique. So, the teacher and students collaborate in exploring various grammatical of English materials. By using small group interaction, it has shown the students’ performance in learning grammar achievement.